Analysis of influence of climatic terms’ changes is on the oxygen mode of Psel river - Степова, О. В.; Рома, В. В. (Scientific Progress & Innovations, 2018)
The climate of the planet is a complex system that changes as a result of processes of interaction between the atmosphere, the ocean and man. These elements are in a balanced equilibrium, which is now being destroyed by man's human activity. The urgency of the theme is due to the necessity of determining changes in the hydrological, hydrochemical and hydroecological state of water objects of Ukraine in the conditions of anthropogenic influence and global warming in order to optimize the management of water resources. The purpose of the research is to study the impact of climate change on the quality of water resources of Psel river, depending on the temperature regime and rainfall in Poltava region. The paper examines the effects of global warming, namely changes in the temperature regime of air and rainfall on qualitative and quantitative characteristics of Psel river in the territory of Poltava region. Using statistical methods, the existence of a correlation between climate parameters and qualitative characteristics of the reservoir has been proved. The results of the research should be taken into account when developing the schemes of adaptation of the region to the conditions of global warming and in the management of water protection activities in the basin of Psel river. The practical value of the results is to provide estimates of changes in the characteristics of the water resources of Psel river; detecting the effects of climate change on the hydrological, hydrochemical and hydroecological regimes of the river; establishing interrelationships between raising the average annual water temperature and the oxygen regime of the reservoir. The results of the work in the future will be used in the development of regional environmental programs and schemes for optimizing the management of water resources.